News as culture : journalistic practices and the remaking of Indian leadership traditions - Rao, Ursula (Anthropology of media, 2010)
At the turn of the millennium, Indian journalism has undergone significant changes. The rapid commercialization of the press, together with an increase in literacy and political consciousness, has led to swift growth in the newspaper market but also changed the way news makers mediate politics. Positioned at a historical junction where India is clearly feeling the effects of market liberalization, this study demonstrates how journalists and informants interactively create new forms of political action and consciousness. The book explores English and Hindi newsmaking and investigates the creati.